THE EFFECT OF CLIMATE CHANGE ON THE AGRICULTURAL SECTOR IN TURKEY - Peker, Ayşe Esra; Er, Ayşe (Society for Innovative Agriculture, University of Agriculture, 2021)
After Industrial Revolution, severe increases were experienced in fossil fuel consumption due to increased energy needs. The endless struggle of humankind for interest and his/her ignorance of environmental devastation led greenhouse gas to accumulate in the atmosphere, global warming to be experienced and, depending on this, climatic change to form. This process experienced has caused many international and national studies to be conducted in the area of climatic change related to the different disciplines, and the issue has taken place in the top orders among the leading subjects in academic platforms. This study discussed the effect of climatic change in Turkey on the agricultural sector. The sectors dealt with the study the agricultural sector, and the effects of climatic changes were aimed to be introduced with an econometric model. In agricultural sector, the effects of climatic changes from the perspective of the product productivity were analyzed by means of the agricultural sector, the effects of climatic changes from the perspective of product productivity were analyzed through Granger Causality Test. In the study, the period of 1970-2017 was based on. The study deals with the issue on a sectorial basis; additionally, its effect is evaluated on the basis of product productivity from the original aspect of the study. Setting out from the results obtained in the study, climatic policies directed to the agricultural sector for Turkey were formed. The effects of the process on the sector were explicitly introduced. Developing climatic policies directed to this sector was targeted to contribute to the literature. © 2021 Society for Innovative Agriculture, University of Agriculture. All Rights Reserved.
Keywords: agricultural products; Climate change; granger causality test; variance decomposition